The rape of the text - Solomon, Harry M. (Univ. of Alabama Press, 1993)
First published in 1733-1734, An Essay on Man, Alexander Pope's best-known philosophical poem was highly praised by many of Pope's European contemporaries, including Voltaire, Rousseau and Hume. The poem, divided into four Epistles, deals with the nature of man and his place in the universe, man as an individual, man in society, and man in pursuit of happiness. Voltaire called An Essay on Man
Keywords: Pope; Alexander <1688-1744>; Pope; Alexander; Essay on man; An essay on man; An essay on man (Pope); Geschichte; Human beings in literature; Philosophy in literature; Philosophy; English